Fermentation quality of Pennisetum purpureum cv. Mott ensiled with Lactobacillus plantarum and sugarcane molasses in tropic - A, Wahyudi; L, Hendraningsih, Sutawi; Setyobudi, Roy Hendroko; Maizirwan, Mel (IOP Publishing, 2019)
Fermentation quality of Pennisetum purpureum (Schumach) cv. Mott ensiled with Lactobacillus plantarum [(Orla-Jensen) Bergey et al.] and sugarcane molasses in tropical condition was evaluated. Approximately 100 g portion of wilted material chopped into 20 mm lengths packed into plastic film bags and sealed with a vacuum sealer. T0 was untreated silage, T1 silage with 50 μL L. plantarum without molasses, and T2, T3, and T4 treated silage with 50 μL L. plantarum and 1 %, 2 %, and 3 % molasses respectively. The bag silos were stored in room temperature (average 25 °C) for 30 d of incubation. This study showed the chemical characteristics were not significantly differ among treatments, eventhough T3 and T4 showed higher organic matter (OM) and water soluble carbohydrate (WSC) contents, meanwhile the highest crude protein (CP) was reached in T3. In general, molasses increased population of lactid acid bacteria (LAB) and decreased pathogen (coliform and aerob bacteria). The favour pH for silages (< 4) were only reached in addition 2 % and 3 % of molasses. It could be concluded that in tropical condition, L. plantarum it self could not improve silage quality. Addition 1 % to 3 % molasses improved silage quality, so that molasses were needed to improve fermentation quality of the grass silage with L. plantarum inoculation.